A cytogenetic study on workers in leather tanning industry - Ismail, Noor H. (Iraqi Journal of Cancer and Medical Genetics, 2016)
Peripheral blood samples were obtained from thirty three leather tannery workers directly involved in the tanning process in the tanning factory at Al- Zaafarniya / Baghdad , one of the factories of state company for leather tanning industries. In addition peripheral blood from twenty healthy control individuals (not known to be exposed to chemicals or other potentially genotoxic substances) were used as control group. The micronucleus (MN) assay was performed using the cytochalasin B technique. We observed a highly significant increase in the mean frequency of lymphocyte micronuclei (MN) and nucleoplasmic bridges (NPBs) , a significant increase in the mean frequency of nuclear buds (NBUDs) and a highly significant decrease in the mean frequency of nuclear division index (NDI) of the tannery workers group in comparison with the control group. The results of the present study also indicate the influence of service duration of tannery workers in lymphocyte MN , NPB, NBUD and NDI frequencies . The age of tannery workers also effect in lymphocyte micronuclei and nuclear division index frequency. The conclusion from our study that the tannery factory workers studied have experienced genotoxic exposure, which is manifested as an increase in the frequency of lymphocyte MN, NPB, NBUD and a decrease in NDI this work shows a clear genotoxic effect. Our study recommends providing all occupational safety requirements for workers in the factory and commitment of workers apply them.